HAMBATAN DALAM PENYIDIKAN TINDAK PIDANA PENIPUAN MELALUI INTERNET - Simarmata, Berlian (Universitas Katolik Santo Thomas Medan, 2020)
There are internal and external barriers to investigating criminal acts through the internet. Internal barriers in the form of a lack of education and knowledge of investigators on the internet itself, while external barriers can be in the form of locus delictinya can be abroad, investigative equipment that often lags behind the sophistication of the tools used by perpetrators of crime, damage to computers and/or mobile phones as goods evidence so that it cannot be used anymore, the difficulty of obtaining witnesses' testimonies who saw the transaction for themselves, as well as expert statements that require large costs.